Changing Patterns of lung, liver, and head and neck non-AIDS-defining cancers relative to HIV status in Tanzania between 2002-2014. Issue 1 (December 2016) - Campbell, Julee; Soliman, Amr; Kahesa, Crispin; Harlow, Sioban; Msemo, Diwani
Abstract Background Tanzania, like other low-income countries, has an increasing cancer burden that remains underestimated. Infection-associated malignancies, particularly HIV-infection, represent a great proportion of cancer burden in Tanzania and throughout Africa. Availability of HIV treatment and improved survival of HIV patients are suggested factors related to increasing prevalence of non-AIDS-defining cancers (NADCs). This study examined patterns of NADCs and proportions of HIV-positivity at the Ocean Road Cancer Institute (ORCI). Methods We reviewed logbooks of all ORCI patients diagnosed and/or treated for lung, liver, and head and neck cancers during 2002–2014. The number of total cancers diagnosed at ORCI during this period was used to calculate proportions of NADCs. We abstracted medical records to obtain demographic and clinical profiles and HIV status information for 1127 patients diagnosed or treated during 2010–2014. Trends in numbers and proportions of NADCs were analyzed using Joinpoint regression. Characteristics of NADC patients were analyzed using multinomial logistic regression. Results NADCs diagnosed at ORCI increased by 33.8% from 2002 to 2014 while the proportion of NADCs relative to all cancers significantly decreased from 6.8% in 2002 to 5.6% in 2014 (APC = -2.74%). Numbers and proportions of lung and liver cancers increased compared to all cancer diagnoses from 2002 to 2014. The number of head and neck cancers increased while decreasing proportionally compared to all cancer diagnoses from 2002 to 2014. Among patients with pathologically confirmed NADCs between 2010 and 2014, HIV prevalence showed a non-statistically significant decrease from 8.1 to 7.1% (APC = -3.77%). Conclusions Absolute numbers of lung, liver, and head and neck cancers increased at ORCI by 1/3 since 2002. Improving survivorship of HIV patients and varying immunodeficiency status may have contributed to the increasing number of NADCs. Total cancer diagnoses nearly doubled during this period, leading to a smaller relative proportion of NADCs diagnosed in 2014 compared to 2002. Late- stage diagnosis and short survival of NADCs included this study may explain possible underestimation and smaller increase in proportion of these particular NADCs compared to other NADCs studied in Tanzania. The slight decrease in proportion of HIV-positive NADC patients during 2010–2014 may suggest increasing patient longevity and more effective HIV management in Tanzania.